2012
DOI: 10.1371/journal.pone.0033849
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Membrane Surface Potential of PC12 Cells as Measured by Kelvin Probe Force Microscopy

Abstract: The plasma membrane of a cell not only works as a physical barrier but also mediates the signal relay between the extracellular milieu and the cell interior. Various stimulants may cause the redistribution of molecules, like lipids, proteins, and polysaccharides, on the plasma membrane and change the surface potential (Φ s ). In this study, the Φ s s of PC12 cell plasma membranes were measured by atomic force microscopy in Kelvin probe mode (KPFM). The skewness val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…FDA can permeate the intact cellular membrane freely, and then be decomposed as fluorescein (with polarity and fluorescence) by the lipase inside the cell. The length of the cell bodies was 9.8 ± 1.2 µm (N = 10), which corresponds with well with previous results (Jeon et al, 2010;Tsai et al, 2012;Zhao et al, 2019b). The green fluorescence can be induced by fluorescein.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…FDA can permeate the intact cellular membrane freely, and then be decomposed as fluorescein (with polarity and fluorescence) by the lipase inside the cell. The length of the cell bodies was 9.8 ± 1.2 µm (N = 10), which corresponds with well with previous results (Jeon et al, 2010;Tsai et al, 2012;Zhao et al, 2019b). The green fluorescence can be induced by fluorescein.…”
Section: Resultssupporting
confidence: 92%
“…The cells were comprised by the cell bodies and processes. The length of the cell bodies was 9.8 ± 1.2 µm (N = 10), which corresponds with well with previous results (Jeon et al, 2010;Tsai et al, 2012;Zhao et al, 2019b). The processes (depicted by white arrows in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Recently, Tsai et al . () showed that KPFM can be applied to analyze the physiological conditions of the plasma membrane in response to various stimulants.…”
Section: Methodsmentioning
confidence: 99%
“…Negatively charged surfaces prevent the attachment of Bacillus thuringiensis spores to mica, silicon, and gold 6 . Changes in cellular membrane potential are indicative of changes in cellular attachment and motility 5,7 . It has been observed that electrically homogeneous surfaces more readily promote microbial adhesion 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Samples do not necessarily have to be conductive (i.e., biological samples). Imaging can be carried out on mica, glass, and silicon surfaces (non-conductive) as long as the non-conductive surface is thin and there is an underlying conductive material 6,7 . The CPD is equivalent to the surface potential voltage and can be described as the difference in the work functions between the tip (φ tip ) and sample (φ sample ), divided by the negative electron charge (-e).…”
Section: Introductionmentioning
confidence: 99%